ANALISIS LITERATUR MENGENAI HUBUNGAN KOMPETENSI AUDITOR DAN KUALITAS AUDITANALISIS LITERATUR MENGENAI HUBUNGAN KOMPETENSI AUDITOR DAN KUALITAS AUDIT - Polapa, Lianti; Bilondatu, Nikma; Radjak Masjhur, Mohamad Abdul (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to conduct a Systematic Literature Review (SLR) to identify research trends, methodological approaches, and patterns of empirical findings regarding the relationship between auditor competence and audit quality. The study follows the PRISMA guidelines in the processes of identification, selection, and synthesis of the literature. The literature search was carried out through the Scopus, Web of Science, ScienceDirect, and Google Scholar databases, covering publications from 2020 to 2025. Articles were selected based on predetermined inclusion and exclusion criteria, resulting in 35 studies being analyzed using thematic analysis and narrative synthesis approaches. The results of the review indicate that auditor competence generally has a positive effect on audit quality, particularly through aspects of professional knowledge, audit experience, and auditors’ technical skills. The literature also shows that this relationship is often influenced by other factors such as auditor independence, professional skepticism, and time pressure in audit execution. In addition, most studies employ a quantitative survey-based approach, while qualitative studies remain relatively limited. This review also identifies variations in findings influenced by differences in research contexts and variable measurement methods. Overall, this SLR provides a comprehensive synthesis of the relationship between auditor competence and audit quality and highlights the importance of developing auditors’ professional competence to improve audit quality. These findings have implications for future research, audit practice, and policy development in enhancing professional auditing standards.